LCMS/MS metabolite profiling and analysis of acute toxicity effect of the ethanolic extract of Centella asiatica on zebrafish model - Zakaria, Fauziahanim; Wan Ibrahim, Wan Norhamidah; Ismail, Intan Safinar; Ahmad, Hafandi; Manshoor, Nurhuda; Ismail, Nor Hadiani; Zainal, Zurina; Shaari, Khozirah (Universiti Putra Malaysia Press, 2019)
Centella asiatica or known as 'pegaga' in Malaysia, is a popular medicinal herb, which is being used as main ingredient or incorporated into various herbal products. Apart from efficacy, the chemical profile and potential toxic effect of the plant are two important aspects of concern towards ensuring product satisfaction and safety of consumers. This paper reports the qualitative and quantitative chemical analysis of the leaf ethanolic extract of C. asiatica using LCMS/MS. The acute toxiciy effect of the extract and selected marker chemical constituents were further analysed using a zebrafish model. Twenty constituents, were identified and the main chemical marker constituents of the plant viz asiaticoside, asiatic acid, and madecassic acid were further quantified. Asiaticoside was found to be present in higher concentration than the other marker constituents. Meanwhile in the acute toxicity test, the LD50 of the extract on the zebrafish model was determined to be 1250 mg/L while 100% mortality was observed at the highest test concentration of 2500 mg/L. However, acute toxicity evaluation on four marker triterpenoids of the herb, i.e asiatic acid, madecassic acid, asiaticoside and madecassoside, indicated them to be quite safe on the zebrafish model, with no mortality shown for test concentrations between 10 to 500 mg/kg BW.